10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
People with lived experience are increasingly recognized as essential contributors to mental health research. Although a growing body of literature, including frameworks and guidance documents, address lived experience involvement, no existing work has systematically identified and defined the distinct roles through which people with lived experience engage in mental health research. This conceptual essay combines a narrative review of peer-reviewed and grey literature with the collective practice-based experience of the author team as lived experience contributors. The Framework for Lived Experience Roles in Mental Health Research (FLER-R) was iteratively developed and refined through collaborative consensus-building among the authors. FLER-R delineate and describe five roles which people with lived experience may undertake in mental health research, supporting the structural embedment of lived experience across mental health research practices.